PERBEDAAN MOTIVASI KERJA GURU PNS DAN NON PNS DILIHAT DARI KEPEMIMPINAN, KEPUASAN GAJI DAN LINGKUNGAN KERJA - Wahyuningsih, Sri -; Wibowo, Edi - (Universitas Slamet Riyadi, 2011)
ABSTRACT The purpose of this study were: (1) analyze the differences in motivation between civil servants and non-civil servant teachers in elementary school views of leadership, pay satisfaction and work environment. (2) analyze the motivation of civil service teachers are better than non-civil servant teachers' work motivation in elementary school views of leadership, pay satisfaction and work environment. The population is all teachers consisting of 254 teachers and 119 teachers PNS non civil servant in a public elementary school district education office UPT Nguter Sukoharjo district. Samples taken are 64 samples of civil servant teachers and 30 samples of non-civil servant teachers. The sampling procedure with proportional cluster random sampling method. The analysis technique uses test validity, reliability test and independent sample t-test. The results showed that: (1) the average civil servant job motivation is higher than non-civil servant teachers 'work motivation in terms of leadership, (2) the average civil servant job motivation is higher than non-civil servant teachers' work motivation in terms of pay satisfaction. The test results independent sample t test showed a significant difference motivation civil servant and non-civil servant teachers in terms of pay satisfaction. The results showed that the average civil servant job motivation is higher than non-civil servant teachers' work motivation in terms of the working environment. The test results independent sample t test showed a significant difference motivation civil servant and non-civil servant teachers in terms of working environment Keywords: motivation, leadership, pay satisfaction, work environment